Early Rabbinic Civil Law - Lapin, Hayim (Brown Judaic Studies, 2020)
This study focuses on tractate Baba Mesi'a' of the Mishnah, which deals primarily with contracts of various kinds. Lapin's book focuses both on the literary traits of the tractate and, more importantly, attempts to tease out some of the implications of the tractate's depiction of social and economic relationships for an understanding of the history of later Roman Palestine.